UPGRADING EFL LEARNERS’ SPEECH SKILLS USING ELECTRONIC DICTIONARIES AND PODCASTS - Suseno, Edy (Innovare Journal of Social Sciences, 2024)
The majority of EFL students have trouble expressing their opinions. Poor hearing, pronunciation, and vocabulary skills are the causes of it. They used electronic dictionaries and podcasts to promote conversation so they could help repair it. An application of WhatsApp group was made to begin the course. On the screen, the instructor displayed the podcast’s URL. The content of the dialog and monolog was then taught to the students. To understand them both in the text and the audio, it was advised that they use their electronic dictionaries. The instructor then extended an invitation to the pupils to use the Google Meet tool. He gave them the task of locating the transcript’s examples of real-life issues. The students were then asked to propose possible fixes for the problems. Following the discussion, the teacher provides feedback on the students’ presentations in the WhatsApp group. The interaction with podcasts and electronic dictionaries helped students develop their speaking skills, according to a qualitative examination of the questionnaire responses and information gathered from the observation. These insights can be used by the teachers to include the relevant subject matter in their lessons. It also encourages additional researchers to conduct pertinent research.